Are Generic UX Evaluation Techniques Enough? A study on the UX Evaluation of the Edmodo Learning Management System - Nakamura, Walter T.; Marques, Leonardo C.; Rivero, Luis; de Oliveira, Elaine H. T.; Conte, Tayana (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2017: Anais do XXVIII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2017.1007, 2017)
As technology evolves and new interaction patterns emerge, User eXperience (UX) is becoming more important. Although several UX evaluation techniques have been proposed, there is no enough evidence regarding their adequacy in the e-learning context. This paper presents an analysis of two UX evaluation techniques applied to the Edmodo Learning Management System. We performed a study with 34 students to evaluate the UX of Edmodo and the perceptions of the techniques. Results showed that Edmodo provided a positive UX. However, around 41% of the students reported that they were not able to fully evaluate their UX using the techniques, indicating a need for improvement.